Síntese e caracterização de nanopartículas de ZnO obtidas pelo método de Pechini adaptado e pela decomposição térmica de hidroxissais lamelares - Candeia, Gabrielli Aline Pietro Bom (2021)
Zinc oxide (ZnO) has numerous applications, some of which are in photodetectors, optical sensors, solar cells, photocatalysis, in the area of medicine, biomedicine, cosmetics, antimicrobial materials, photoprotectors, etc. Nanoparticles have been of great interest because they improve properties based on specific characteristics (surface area, particle size, distribution and morphology) and, consequently, the potential applications of these materials. ZnO nanoparticles (NPs-ZNO) were synthesized in this work by thermal decomposition of layered Hydroxisalts (HSLs) and the Pechini adapted method. The purpose of synthesizing NPs by two different methods is to compare the physicochemical properties, morphology and analyze the advantages and disadvantages of each technique. So far, studies using a wide variety of precursors and comparing the two synthesis methods proposed in this work have not been found in the literature. In the first method, Zinc Hydroxybenzoate (HBZ) and Zinc Hydroxysalicylate (HSZ) HSLs were prepared by the precipitation method using different precursor zinc salts (acetate, chloride, nitrate and sulfate) and different intercalated anions (benzoate or salicylate) to observe if there is an impact on the particle size. These samples were characterized using the techniques of DRX, FTIR and Thermal Analysis TGA/DTA. Materials with a basal spacing of 19.2 Å for HBZ samples and 16.0 Å for HSZ samples are obtained. From the thermal analysis it, was possible to define the calcination temperature of the HSLs for the formation of NPs-ZnO being up to 500 °C. The NPs-ZnO obtained by this method were characterized by XRD. The Pechini method also studied the variation of precursor zinc salts (acetate, chloride, nitrate and sulfate), and the samples were calcined up to 700 °C and characterized by XRD. A total of 12 samples of NPs-ZnO were obtained between the two syntheses, and the particle sizes were calculated by the Scherrer Equation. It was observed that, in ascending order of size, the four smallest were samples synthesized from the thermal decomposition of HSLs, the smallest being HBZ-ZnO-C samples of 29.3 nm.